Tutoring Environment for Automata and the Users' Achievement Goal Orientations - Tecson, Cesar A (Archīum Ateneo, 2018)
Studying automata theory exposes the students to the theoretical foundation of Computer Science where they learn abstraction, generalization, and reasoning. However, teaching and learning automata is challenging because of the involved abstract notions and mathematical background. Many students experience difficulty in understanding the computability concepts. Hence, recent advances in teaching the course focus on the development of different pedagogical tools that can be used to facilitate the learning of automata theory and formal languages. Another factor that mediates student achievement is achievement goal orientation. Some students are mastery-oriented and some others are performance-oriented. Both types of learners have different learning needs. This study presents the appeal of the developed tutoring system for automata, ILSA, to the different achievement goal orientations of learners.